Development and validation of a mobile application for heart failure patients self-care - Sousa, Mailson Marques de; Lopes, Camila Takáo; Almeida, André Atanasio Maranhão; Almeida, Taciana da Costa Farias; Gouveia, Bernadete de Lourdes André; Oliveira, Simone Helena dos Santos (Revista da Escola de Enfermagem da USP, 2023)
Objective: To develop and verify content and face validity evidence of a mobile application prototype for heart failure patients self-care. Method: Study of technological development based on Contextualized Instructional Design. In the validation stage, six cardiology specialist nurses evaluated the content through the Suitability Assessment of Materials and 13 people with heart failure underwent face validity assessment, through content validity index. Data were analyzed using descriptive statistics. Results: The prototype of the application, called “Tum Tum”, has an interface and free navigation screens covering the concept of heart failure, its causes, symptoms and signs, diagnosis, and treatment. It has a mosaic with educational guidelines, resources for early recognition of signs of clinical decompensation, registration for body weight control, reminders for medication use, consultation and exam schedule. The technology proved to be adequate among specialists and the target audience. Conclusion: It was possible to develop and validate the content and face of the “Tum Tum” application prototype, which demonstrates the potential to promote self-care in people with heart failure.